New record of potential cyanobacteria from Indian Region falling Indo-Burma Biodiversity Hotspots (North-East Region of India) and Partial Characterization for Value Additions. - Singh, Ojit K.
Cyanobacteria are prokaryotic organisms capable of oxygenic photosynthesis. They appeared to be a rich source for many useful products and are known to produce a number of bioactive compounds. The North-east region of India is a genetic treasure house of plant, animal, and microbial resources. In this study, two hundred study (260) unialgal cyanobacterial isolates from Indian region falling Indo-Burma biodiversity hotspots were characterized and primarily screened. Ten (10) isolates from six genera viz-a-viz, Anabaena (03), Nostoc, (01), Phormidium (03), Plectonema (01), Lyngbya (01), and Microchaete (01) were found to be useful for industrial application. Study show that in the present investigation, Phormidium tenue (Menegh.) Gomont (NEMN138) have showed ammonia content and can be used as biofertilizers. Anabaena fuellebornii Schmidle (NEMN125), Phormidium bohneri Schmidle (NEMN183), Nostoc spongiaeforme Agardh ex Born. et Flah (NEMNI131) were found to be useful for production of phycobiliproteins from cyanobacteria which can be beneficial for industrial applications. All ten isolates have been deposited to the fresh water cyanobacterial and microalgal repository of IBSD, Imphal, Manipur, India (National facility created by Department of Biotechnology, Government of India, in 2009 with reference No. BT/PR 11323/PBD/26/171/2008 dated 31-03-2009) after obtaining accession number.
Keywords: Biodiversity hot spots; Cyanobacteria; Indo-Burma.; North-East India; Repository; Value addition